2021
DOI: 10.1101/2021.03.12.435146
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ca2+-activated sphingomyelin scrambling and turnover mediate ESCRT-independent lysosomal repair

Abstract: Lysosomes are vital organelles vulnerable to injuries from diverse materials. Failure to repair or sequester damaged lysosomes poses a threat to cell viability. Here we report that cells exploit a sphingomyelin-based lysosomal repair pathway that operates independently of ESCRT to reverse potentially lethal membrane damage. Various conditions perturbing organelle integrity trigger a rapid calcium-activated scrambling and cytosolic exposure of sphingomyelin. Subsequent metabolic conversion of sphingomyelin by n… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…SM adopts an asymmetric distribution across the bilayers of late secretory and endolysosomal organelles, with the bulk of SM residing in the luminal/exoplasmic leaflet. However, using GFP-tagged EqtSM as cytosolic SM reporter (EqtSM cyto ), we found that perturbation of lysosome or PM integrity by pore-forming chemicals or toxins disrupts transbilayer SM asymmetry by triggering a rapid transbilayer movement of SM catalyzed by Ca 2+ -activated scramblases (Niekamp et al, 2022). To perform its central task in membrane biogenesis, the ER harbors constitutively active scramblases that enable a rapid equilibration of newly synthesized phospholipids across its bilayer (Pomorski and Menon, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SM adopts an asymmetric distribution across the bilayers of late secretory and endolysosomal organelles, with the bulk of SM residing in the luminal/exoplasmic leaflet. However, using GFP-tagged EqtSM as cytosolic SM reporter (EqtSM cyto ), we found that perturbation of lysosome or PM integrity by pore-forming chemicals or toxins disrupts transbilayer SM asymmetry by triggering a rapid transbilayer movement of SM catalyzed by Ca 2+ -activated scramblases (Niekamp et al, 2022). To perform its central task in membrane biogenesis, the ER harbors constitutively active scramblases that enable a rapid equilibration of newly synthesized phospholipids across its bilayer (Pomorski and Menon, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent conversion of SM to ceramides by neutral SMases on the cytosolic surface of injured lysosomes promotes their repair, presumably by driving an inverse budding of the damaged membrane area in a process akin to ESCRT-mediated formation of intraluminal vesicles. This SM-based membrane restoration pathway functions independently of ESCRT and may also operate at the PM (Niekamp et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The depletion of ESCRT components prevent this shedding and results in death of the cell [ 53 , 58 ]. Intriguingly, an ESCRT-independent repair pathway involving trans-bilayer motion of sphingomyelin on damaged lysosomes has also, recently, been reported [ 63 ].…”
Section: Repair and Removal Of Damaged Endocytic Organellesmentioning
confidence: 99%
“…More recently, SM was reported to be exposed on the cytosolic side of damaged phagosomal membranes around Salmonella or Listeria, with galectin-8 localizing to the phagosomal membranes [176,177]. The cytosolic exposure of SM by Ca 2+activated scramblase was recently reported to mediate lysosomal repair independently of the endosomal sorting complex required for the transport complex (ESCRT) [178]. Although the mechanisms by which pathogenic mycobacteria survive inside host cells remain unclear [179], an exploration of the involvement of cross-talk between GSL-enriched microdomains and other sphingolipids in intracellular events, such as phagosome maturation, may be key to the development of new treatments for mycobacterial infections.…”
Section: Intracellular Interactions Between Gsl-enriched Microdomains and Pathogensmentioning
confidence: 99%